PENGEMBANGAN MEDIA PAPAN CERDAS PERKALIAN PADA MUATAN PELAJARAN MATEMATIKA UNTUK SISWA KELAS II SEKOLAH DASAR - Indriana Indriana; Akmal Rijal; Riduan Febriandi (Primary Education Journal Silampari (PEJS), 2021)
This study aims to develop a product in the form of a Multiplication Smart Board Media on the Content of Mathematics for Grade II Elementary School students in accordance with the 2013 curriculum and to produce a valid and practical multiplication smart board media so that it can be used in learning. This research is a development research with a development model adapted from the 4-D model. Based on the results of the analysis based on the assessment by the three experts, namely: linguists, material experts, media experts, it shows that the smart board media meets the valid criteria with an average of 0.73%. While the results of the analysis of the results of the practicality sheet of teachers and students consisting of 9 people, it was found that the smart board media met the very practical criteria with an average of 96.7%. So it can be ignored that the multiplication smart board media meets valid, practical criteria and can be used in mathematics learning. Keywords: Development, Multiplication Smart Board Media, Mathematics